2020
DOI: 10.1021/acs.joc.0c01254
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Negishi Reaction of Trisubstituted Vinyl Phosphates for the Synthesis of Tetrasubstituted Alkenes

Abstract: The present study investigated the ability of bromovinyl phosphates to react with organozinc reagents at room temperature during palladium-catalyzed reactions. It was determined that both the bromine atom and the phosphate group were successfully substituted by means of the reaction with the organozinc reagents, thereby allowing for the synthesis of cyclic and acyclic tetrasubstituted double bonds. The low stability of the organozinc compounds in an acidic environment was exploited to accomplish the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Bromenol phosphate 1 a can also be used in the Negishi reaction to replace the bromine atom with alkyl and aryl groups, as illustrated in Scheme 3. Our recently developed conditions for the Negishi reaction of cyclic bromoenol phosphates [34b] proved efficient for the conversion of the phosphate 1 a into the ketone 3 d . This approach is sensitive to the preparation of the organozinc reagent, as shown for the compound 3 d , which was obtained in lower isolated yields when starting from 4‐tolylmagnesium chloride.…”
Section: Resultsmentioning
confidence: 99%
“…Bromenol phosphate 1 a can also be used in the Negishi reaction to replace the bromine atom with alkyl and aryl groups, as illustrated in Scheme 3. Our recently developed conditions for the Negishi reaction of cyclic bromoenol phosphates [34b] proved efficient for the conversion of the phosphate 1 a into the ketone 3 d . This approach is sensitive to the preparation of the organozinc reagent, as shown for the compound 3 d , which was obtained in lower isolated yields when starting from 4‐tolylmagnesium chloride.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been employed for the preparation of 2-substituted cyclobutanones [ 82 ] and cyclobutenones [ 83 ]. Further studies have shown that aluminum chloride facilitates the Negishi reaction of cycloalkenyl diphenyl phosphates at room temperature [ 84 , 85 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…In addition, the Perkow reaction [68], which is based on the reaction of halogenated ketones with phosphites, can also be used to prepare vinyl phosphates (Scheme 2b). This is particularly advantageous for the preparation of triple [69,70] and double [71][72][73][74][75][76] electrophilic templates 6 using brominated ketone 5. Cross-coupling reactions are also useful for the introduction of simple fragmentsnamely, the vinyl group.…”
Section: Introductionmentioning
confidence: 99%